The Knowledge Building International Project as an Innovative Learning Environment - Josep Gallifa; Mireia Montané; Sandra Lund; Carme Amorós; Mercè Bernaus; Mercè Gisbert; Francesc Martínez-Olmo (The Canadian Network for Innovation in Education (CNIE), 2021)
The Knowledge Building International Project (KBIP), implemented in a network of eight schools in Catalonia, demonstrates the value of an Innovative Learning Environment (ILE) towards supporting dialogical, technological, and systemic dimensions in teaching and learning. Using a design-based research (DBR) approach, a survey queried teachers, students, and external stakeholders regarding their perceptions about educational innovation. The results provide both the profile and the innovative nature of the whole KBIP experience at each participating school. The main results help illustrate the potential of KBIP methodologies. The findings exemplify the value of this particular DBR method for evaluating educational innovations.